Enhancing transparency and efficiency in green energy management through blockchain: A comprehensive bibliometric analysis - Oliver O. Apeh; Nnamdi I. Nwulu (Energy Nexus)
Blockchain is evolving as a crucial technology in protecting the future outlook of energy systems and global economic competition. As a result of the huge rise in industrial pollution, it has gained extensive consideration from economic establishments, green energy supply organizations, tech designers, governments, and researchers. Stakeholders from various fields identify the potential of blockchain integration with green energy as a tool to transform different activities in the sector, such as reducing the grid's major carbon emissions, freeing cyber theft and generating novelty. Moreover, blockchain system is tamper-proof, transparent, and has the prospect of addressing novel business solutions, mostly when integrated with smart contracts. In this study, 510 documents from 2017 to 2024 were selected and visualized using CiteSpace software and bibliometric approaches to analyze the research field's growth base, hotspot areas, country and their policy implementations, collaborative groups, and evolutionary trends of blockchain base within energy networks. It investigates the existing literature to acknowledge the progress made in the field. The key findings show that basic research on blockchain technology in the energy sector is fast growing with time, showing that integrating blockchain and green energy is an emerging research field. Out of 742 countries and regions, China leads with 89 publications, recording 24.7%, followed by India with 78 publications, accounting for 21.7%, and the United States with 76 publications, accounting for 21.1%. Among them, China's collaborations rely mainly on renewable energy management. Moreover, the practical application cases corresponding to research hotspots are mostly located in developed countries, especially in the United States, the European Union, and Australia. The research gaps in blockchain-based green energy applications are noticed in green certificate trading, micro-grid energy market, technology and policy, energy management, as well as potential trends in energy internet, energy systems, and green power trading. The findings of this paper will assist researchers in gaining a vast knowledge of the present research in the area of blockchain and green energy and identify future research trends in the field. Hence, this will boost the knowledge of energy expansion among energy trading experts, seize possible opportunities, and offer beneficial insights for the government to introduce blockchain advancement and green energy trading policies.